Using cell membrane chromatography and HPLC-TOF/MS method for in vivo study of active components from roots of Aconitum carmichaeli - Yan Cao; Xiao-Fei Chen; Di-Ya Lü; Xin Dong; Guo-Qing Zhang; Yi-Feng Chai (Elsevier, 2011)
An offline two-dimensional system combining a rat cardiac muscle cell membrane chromatography time-of-flight mass spectrometry (CMC-TOF/MS) with a high Performance liquid chromatography time-of-flight mass spectrometry (HPLC-TOF/MS) was established for investigating the parent components and metabolites in rat urine samples after administration of the roots of Aconitum carmichaeli. On the basis ofthe analysis of the first dimension, retention components of the urine sample were collected into 30 fractions (one fraction per minute). Then offline analysis of the second dimension was carried out. 34 compounds including 24 parent alkaloids and 10 potential metabolites were identified from the dosed rat urine, and then binding affinities of different compounds on cell membranes were compared and influences of some functional groups on activity were estimated with the semi-quantification and curve fitting method. As a result, binding affinities decreased along with the process of deacylation, debenzoylation and demethylation, which may be related to the alleviation of toxicity in the procedure of herb processing or metabolism. Moreover, some minor components in rat urine (Songorine, 14-benzoylneoline, Deoxyaconitine, etc.) exerted relatively strong affinity on cell membranes are worth exploring. The results delivered by the System suggest that the CMC can be applied to in vivo study. Keywords: cell membrane chromatography, high Performance liquid chromatography, time-of-flight mass spectrometry, two-dimensional system, Aconitum carmichaeli